Efficacy of Cognitive Behaviour Therapy in Managing Test Anxiety and in Enhancing Achievement Motivation among female Nursing Students (International Journal of Food and Nutritional Sciences, 2022)
Background: Many people experience stress or anxiety before, during, and after the exam. Little anxiousness usually helps with better performance. Even so, once this anxiety becomes so extreme that this starts to interfere with academic achievement, it may be necessary to avoid situations involving testing. Test anxiety can cause symptoms of depression, low self-esteem, anger, and a sense of hopelessness. Objective: The current study examined the "efficacy of cognitive behaviour therapy in managing test anxiety, and in enhancing achievement motivation among nursing students. Material and Methods::The participants were selected through the purposive sampling technique. The study population included first-year Bsc nursing students from Baby Memorial College of Nursing, Kozhikode, Kerala, India. They were assessed on Test Anxiety developed by Sharma (2000) and Achievement Motivation constructed by Bhargava (2009).Research Design: The Experimental research design method before, after and follow-up without control group design were selected for the present study. Cognitive behaviour therapy was given once a day for about 60 minutes a week. The researcher exposed students to mindfulness, breathing exercises, goal-setting and guided imagery meditation. Results: The Repeated Measure ANOVA For test anxiety and achievement motivation results revealed that significant differences were observed in all three phases (before, after, and follow-up). Conclusion Cognitive behaviour therapy was found to be effective in reducing test anxiety and enhancing achievement motivation among nursing students. This supports policymakers maker, universities, institutions, and colleges to organize more CBT workshops.